2023
DOI: 10.4081/ripppo.2023.704
|View full text |Cite
|
Sign up to set email alerts
|

Epistemic trust: a comprehensive review of empirical insights and implications for developmental psychopathology

Elizabeth Li,
Chloe Campbell,
Nick Midgley
et al.

Abstract: Originally rooted in philosophy and sociology, the concept of epistemic trust has recently transitioned to developmental psychopathology, illuminating social-cognitive processes in psychopathology. This narrative review synthesizes empirical evidence on epistemic trust to inform future research. A literature search highlighted 3 areas: i) the development of selective trust in children; ii) epistemic trust in non-clinical adults; iii) its link to mental health. Young children demonstrate selective learning from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 165 publications
0
3
0
Order By: Relevance
“…This interaction between the patient and healthcare provider helps to reduce the patients' innate epistemic vigilance toward new information, fostering a space of openness and receptivity. This is exemplified in psychotherapy, where it's observed that patients who trust their therapists to provide relevant and applicable information are more likely to engage in the therapy process and achieve better outcomes (Riedl et al, 2023;Li et al, 2023). This is particularly important to be considered in the context of patients with comorbid mental disorders.…”
Section: Epistemic Trust In Chronic Illness Managementmentioning
confidence: 99%
“…This interaction between the patient and healthcare provider helps to reduce the patients' innate epistemic vigilance toward new information, fostering a space of openness and receptivity. This is exemplified in psychotherapy, where it's observed that patients who trust their therapists to provide relevant and applicable information are more likely to engage in the therapy process and achieve better outcomes (Riedl et al, 2023;Li et al, 2023). This is particularly important to be considered in the context of patients with comorbid mental disorders.…”
Section: Epistemic Trust In Chronic Illness Managementmentioning
confidence: 99%
“…Thus, the child learns not only to perceive their caregiver as a reliable source of information but also to benefit from positive influences in their environment more generally ( Luyten et al, 2020 ). This characteristic of secure attachment relationship is often lacking in adverse childhood experiences and insecure attachment, which have strong and positive associations with epistemic mistrust and epistemic credulity ( Li et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the child learns not only to perceive their caregiver as a reliable source of information but also to benefit from positive influences in their environment more generally (Luyten et al, 2020). This characteristic of secure attachment relationship is often lacking in adverse childhood experiences and insecure attachment, which have strong and positive associations with epistemic mistrust and epistemic credulity (Li et al, 2023).…”
Section: Introductionmentioning
confidence: 99%